2021
DOI: 10.1038/s41598-021-99586-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipidomic profiles of kidney, breast and prostate cancer patients differ from healthy controls

Abstract: Early detection of cancer is one of the unmet needs in clinical medicine. Peripheral blood analysis is a preferred method for efficient population screening, because blood collection is well embedded in clinical practice and minimally invasive for patients. Lipids are important biomolecules, and variations in lipid concentrations can reflect pathological disorders. Lipidomic profiling of human plasma by the coupling of ultrahigh-performance supercritical fluid chromatography and mass spectrometry is investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…For example, SM 41:1;O2 and SM 42:1;O2 are downregulated in both sample matrices, while lower levels of multiple other SM are observed in plasma rather than in the tumor tissue. Reduced levels of SM in RCC have been documented before [11,43], and these findings suggest that SM levels and alteration of the synthetic and degradative pathways play an essential role in cancer. It was reported that SM accumulate in the HCT-116 (human colon cancer cell lines) during apoptosis [44].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, SM 41:1;O2 and SM 42:1;O2 are downregulated in both sample matrices, while lower levels of multiple other SM are observed in plasma rather than in the tumor tissue. Reduced levels of SM in RCC have been documented before [11,43], and these findings suggest that SM levels and alteration of the synthetic and degradative pathways play an essential role in cancer. It was reported that SM accumulate in the HCT-116 (human colon cancer cell lines) during apoptosis [44].…”
Section: Discussionmentioning
confidence: 92%
“…Solvents for extraction were purchased from Sigma-Aldrich (St. Louis, MI, USA). For lipid extraction from 25 µL of plasma, a modified Folch method with a chloroformmethanol-water mixture was employed [11]. The samples were spiked before extraction with a mixture of internal standards obtained from Avanti Polar Lipids (Alabaster, AL, USA) to achieve final concentrations of 0.1 nmol of SHexCer 18:1;O2/12:0 and 43.3 nmol of SM 18:1;O2/12:0 per mL of plasma.…”
Section: Sample Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of ethanolamine-containing phospholipids, including PEs, LPEs and PE plasmalogens, were significantly low in four cancer types but high in thyroid cancer, thus reinforcing the idea that plasma lipidomics may reveal features common to different types of cancer, as well as cancer-specific features. Wolrab et al investigated the plasma lipidomic profiles of breast, kidney and PCa patients, finding that the most significant lipid species for cancer separation were CE 16:0, Cer 42:1, LPC 18:2, PC 36:2, PC 36:3, SM 32:1, and SM 41:1, all down-regulated in the plasma of patients as compared to controls, thus representing a potential biomarker panel for breast, kidney and PCa screening [ 74 ].…”
Section: The Lipidome Of Biofluids As a Source Of Potential Cancer Bi...mentioning
confidence: 99%
“…Furthermore, GSL with blood group determinants is well known to be synthesized at high levels in the pancreas ( 20 ). Aberrant expression of GSL including alterations in the composition and concentrations of GSL and lipids is a typical hallmark of a wide range of cancers ( 7 , 14 , 21 , 22 , 23 , 24 , 25 ), which has been extensively documented in cancer cell lines ( 22 , 26 , 27 , 28 , 29 ) or tissues ( 20 , 24 , 30 , 31 , 32 , 33 , 34 ) and also reported in body fluids of cancer patients ( 35 , 36 , 37 , 38 ). Several of the studies mentioned above concluded that the reported dysregulation of lipid metabolism in cancer cells is relevant to distinguish cancer patients from healthy controls, suggesting that changes in lipidomes are strongly associated with cancer progression ( 6 ).…”
mentioning
confidence: 99%